Exploring Cultural Conflict Resolution through Face Negotiation Theory in the Indonesian Film ‘Tarung Sarung’ - Made Dwi Adnjani; Muna Yastuti Madrah; Ahmad Mujib (Jurnal the Messenger, 2025)
Introduction: This study examines Islamic values and intercultural communication through the lens of Face Negotiation Theory (FNT) in the film ‘Tarung Sarung’ (‘Sarong Fighting’). As a medium of communication, film delivers embedded messages that influence audience perceptions and emotions. ‘Tarung Sarung’ reflects societal realities and conveys messages that foster understanding across cultures. Indonesia's cultural diversity often leads to conflicts rooted in stereotypes, highlighting the need for cultural approaches to conflict resolution.